Paradigms and Postmodern Politics from an Islamic Perspective (American Journal of Islam and Society, 1991)
The paradigm shifts from the 1950s to the 1980s in political science arebest explained with reference to the encounter with the Other, an encounterwhich has three stages: first, the self-confident representation of the Otherwhich is characteristic of modernity; second, the fear of and desire to controlthe Other which is characteristic of the end of modernity; and third, thehyperrealization and trivialization of the Other which is characteristic ofpostmodernity. This encounter with the Other takes place within a largerdiscourse context or episteme. The epistemic shifts, then, must also beconsidered.Paradigm ShiftFoucault’s concept of archaeology includes the idea that scientific systemsare valid within their own contexts. Thus each piece of historical data mustbe judged and assessed in its own stratum or context. In a less sophisticatedfashion, Kuhn has taken this idea of historical context and cultural relativismand come up with a theory of scientific revolution. Kuhn correctly identifiesthe science textbook genre as the received history of normal science, a genrewhich incorporates the myth of the steady cumulative process of science.The textbook mythology traces the history of great white men and greatexperiments as they contributed their energies to the irresistible march ofscientific progress. Kuhn demonstrates that Aristotelian dynamics or caloricthermodynamics are in fact internally systematic and scientific and are thereforejust as valid as contemporary dynamics or thermodynamics. In reference totheir “fit” with nature, an earth-centered astronomy is just as valid as a suncenteredastronomy. What happens is that when the questions change, andquestions are asked which strain an earth-centered astronomy, a paradigm ...